Response time optimization with Internet-of-Things-based wireless sensor network emergency alert system for firefighter - Sainuddin, Nurulidayu (2024)
Disasters and emergencies often have a significant impact on the environment and livelihoods, necessitating a rapid emergency response. To ascertain the best outcomes, emergency event reporters and firefighters must respond effectively to minimize adverse impacts and facilitate a swift recovery, in line with the firefighter's key performance indicator which is under 10 minutes. However, manual handling in control rooms introduces delays and human errors. Thus, this research developed an Internet-of-Things (IoT) based Wireless Sensor Network (WSN) emergency alerting system for firefighters which consists of one base station and three sensor nodes to enhance firefighter’s response time. Results showed that the average firefighter’s response time had improved to 8.54 minutes compared to the previous response time of 15.48 minutes with the usage of the automated IoT-based emergency alert system. In addition, as wireless data transmission in firefighting stations is prone to radiofrequency (RF) interference and collision due to obstacles, limited bandwidth, and shared medium, this research proposed a node addressing scheme with the deployment of Time Division Multiple Access (TDMA) to help manage access to the wireless medium, reduce collisions, and improve the overall reliability of data transmission. As a result, a reduction of 12% packet loss rate was observed for outdoor and indoor transmission when a sample of 100 data packets was transmitted. Lastly, the coverage of radio frequencies is subject to certain limitations and considerations which include type of antenna usage, baud rate setting, node placement, and power control. Consequently, this research studied the network coverage for point-to-point and multipoint transmission in indoor, outdoor, and indoor-outdoor environments. The findings in all environmental scenarios signified that the transmission coverage showed an upward trend when the transmission power was increased. An 8.8% of improvement was seen when transmitting with 20dBm in the outdoor scenario compared to an indoor scenario, which is aligned with the hypothesis that the coverage can be improved with a higher transmission power and suitable node placement. In conclusion, this research improved the average response time of the firefighters by 6.56 minutes, reduced the data collision within the network by 12%, and increased the transmission coverage by 8.8%.